Expression of Ki-67 in Oral Lichen Planus: A Systematic Review and Meta-Analysis - Ayla Bahramian; Paria Motahari; Aliraza Hanifenezhad (Journal of Dentistry)
Statement of the Problem: One of the main signs of cancer development is increasing of cell proliferation activity. Expression of the Ki-67 as a cell proliferation marker is extensively utilized in pathology studies as an indicator of proliferation in human tumors. According to studies, Ki-67 plays an effective role in the pathology of malignant and pre-malignant oral mucosa lesions.Purpose: The current study aimed to systematically review the Ki-67 expression in oral lichen planus without dysplasia and compare it with oral epithelial dysplasia.Materials and Method: In this meta-analysis, all articles in the English language were searched in databases including Web of Science, PubMed, Embase, Scopus, and Google Scholar until July 2023. MeSH terms and free keywords were used in the search step. Expression of Ki-67 in oral lichen planus and oral epithelial dysplasia was analyzed by Comprehensive Meta-Analysis software.Results: Nine hundred and two articles related to the searched words were found. According to the selection criteria, 12 retrospective articles were selected. Low quality was not observed in any of the records by the Newcastle-Ottawa scale and most of them had a relatively good quality. Totally, 593 patients were examined. The heterogeneity between studies was not significant. The meta-analysis results indicated a significantly lower Ki-67 expression in oral lichen planus without dysplasia in comparison to oral epithelial dysplasia.Conclusion: The more intense expression level of Ki-67 in oral epithelial dysplasia compared with oral lichen planus was observed. The ki-67 expression could be utilized to indicate the existence and intensity of epithelial dysplasia and disease progression.